Training EFL Pre-Service Teachers in Using AI Tools to Create Digital Narrative Teaching Materials - Nikmah, Lailatul; Isnawati, Ida; Ningsih, Fitria (English Language Education, Universitas Internasional Batam, 2025)
Artificial Intelligence (AI) has been increasingly used to support EFL material development, yet many pre-service teachers often lack the skills to integrate it effectively. In response to this need, this study examines the implementation and impact of a structured AI-integrated training session to develop digital storytelling (DST) competencies. Using a mixed-methods approach, the research involved 90 EFL pre-service teachers participating in AI training sessions that followed a five-stage workflow: prompting, voice-over creation, image generation, video editing, and lesson planning. Data were collected from training observations, analysis of 23 DST projects, and a 10-item Likert-scale satisfaction survey. Findings show that participants successfully produce multimodal narrative DST using 4-7 AI tools per project, such as ChatGPT, Canva AI, AI Video Cloud, and Magic School AI, to produce diverse digital narrative materials. The digital products targeted students and designed pedagogically aligned lesson plans for Grades 2 to 12 that assessed multiple English skills, with listening and reading being the most frequently integrated. Fables were also the most selected genre, followed by romance, fantasy, and fairy tales. Survey results indicate a high level of satisfaction (M=4.25), confidence, and perceived usefulness of AI tools for EFL material development. The study highlights the pedagogical potential of integrating AI-driven tools in EFL teacher preparation and suggests practical implications for curriculum design in teacher education programs.